A previously undescribed de novo insertion-deletion mutation in the beta myosin heavy chain gene in a kindred with familial hypertrophic cardiomyopathy. Issue 5 (November 1996) - Cuda, G.; Perrotti, N.; Perticone, F.; Mattioli, P. L.
Abstract : A previously undescribed de novo insertion-deletion mutation in the beta cardiac myosin heavy chain gene was found in a kindred with familial hypertrophic cardiomyopathy. In the mutated allele there is an inserted-deleted guanine at nucleotides 8823 and 8850 of the beta myosin heavy chain gene, resulting in a dramatic change of the amino acid sequence (AA 395-404). such a mutation, detected in the proband and in his son but not in the proband's parents, is likely to produce major impairment of myosin function.